Human-in-the-loop optimization of exoskeleton assistance during walking - Zhang, Juanjuan; Fiers, Pieter; Witte, Kirby A.; Jackson, Rachel W.; Poggensee, Katherine L.; Atkeson, Christopher G.; Collins, Steven H. (Science (American Association for the Advancement of Science), 2017)
Exoskeletons and active prostheses promise to enhance human mobility, but few have succeeded. Optimizing device characteristics on the basis of measured human performance could lead to improved designs. We have developed a method for identifying the exoskeleton assistance that minimizes human energy cost during walking. Optimized torque patterns from an exoskeleton worn on one ankle reduced metabolic energy consumption by 24.2 ± 7.4% compared to no torque. The approach was effective with exoskeletons worn on one or both ankles, during a variety of walking conditions, during running, and when optimizing muscle activity. Finding a good generic assistance pattern, customizing it to individual needs, and helping users learn to take advantage of the device all contributed to improved economy. Optimization methods with these features can substantially improve performance.